2006
DOI: 10.1097/01.coh.0000194362.59762.24
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of the immune restoration inflammatory syndrome

Abstract: It is important to consider immune reconstitution inflammatory syndrome particularly in patients who are started later on antiretroviral therapy. As HIV-infected patients who present late in their disease course are at risk, consideration of this syndrome is particularly important for developing countries where antiretroviral therapy is often prescribed for patients who already have advanced immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The median duration of immune reconstitution was 17 months. [16][17][18] Patients with lower CD4 counts at baseline, who experienced greater increments in the CD4 counts following HAART, were more likely to develop AITD. But none of the patients in our study was found to have immune reconstitution syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of immune reconstitution was 17 months. [16][17][18] Patients with lower CD4 counts at baseline, who experienced greater increments in the CD4 counts following HAART, were more likely to develop AITD. But none of the patients in our study was found to have immune reconstitution syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In persons with HIV infection, Graves' disease may occur after immune reconstitution from HAART. However, unlike classic immune reconstitution inflammatory syndrome caused by mycobacteria and other pathogens, which develops during the first 3 months of HAART [42,43], Graves' disease is most commonly diagnosed 12-36 months after HAART initiation. The difference in timing may be explained by differences in the type of CD4 cell count that increases during these 2 periods.…”
Section: Increased Thyroid Functionmentioning
confidence: 99%
“…Clinical worsening of infectious syndromes after initiation of ART, or immune reconstitution inflammatory syndrome (IRIS), has been extensively described in the HIV literature. 7 In these patients, initiating ART elicits a pathological inflammatory response to either a previously treated infection or a subclinical infection. IRIS has also been described in patients with MS in the setting of cessation of immunosuppressive medications, often with concurrent PML.…”
Section: Discussionmentioning
confidence: 99%